Evaluation of the root and canal morphology of mandibular permanent anterior teeth in an Iranian population by cone-beam computed tomography. - Mohsen Aminsobhani; Mona Sadegh; Naghmeh Meraji; Hasan Razmi; Mohamad Javad Kharazifard (Tehran University of Medical Sciences, 2013)
To evaluate differences in the root and canal configurations of mandibular permanent anterior incisors and canines in an Iranian population by means of Cone Beam CT (CBCT) images.Four hundred CBCT images of mandibular permanent incisors and canines that met the inclusion criteria were evaluated. Vertucci's classification was used to evaluate the number of roots, number of root canals, root lengths, root curvatures and canal types.Totally 632 central incisors, 614 lateral incisors and 608 canines were evaluated. The average length of the mandibular central, lateral incisors and canines was 21.3±0.10, 21.9± 0.13 and 25.1± 0.11 mm, respectively. All of the mandibular central and lateral incisors had one root, but the incidence of single-rooted mandibular canines and two-rooted mandibular canines was 96.3% and 4.7%, respectively. The majority of mandibular central, lateral incisors and canines had one canal (72.7%, 70.6% and 71.8%, respectively). Five types of Vertucci canal configurations were seen in the evaluated teeth. Type 1 Vertucci configuration was the most prevalent configuration (72.3%, 70.6% and 71.8% for the central, lateral incisors and canines, respectively)), and type 5 Vertucci canal configuration was the least prevalent type seen (3.3%, 3.2% and 2.3% for the central, lateral incisors and canines, respectively). The most frequent root curvatures in these teeth were distally and buccally. No significant difference was seen between male and female patients regarding any of the parameters evaluated in this study (p>0.05).More attention should be given to the detection of additional canals and the recognition of canal curvature in Iranian patients.